Chapter Educazione degli Adulti e Tecnologie dell'Educazione: intersezioni disciplinari tra passato, presente e futuro - Ranieri, Maria (Studies on Adult Learning and Education, 2022)
The essay shows the historical and theoretical connections between adult education and distance learning, showing how the latter has made use of the many theories developed since the Andragogic challenge and how it has been able to offer itself as a catalyst for the former. Especially starting from MOOCs, this dual nature of distance learning - that of concretizer and that of reflective catalyst of adult education - are transformed into a research that touches pedagogical aspects (related to continuing education and its strategic role), teaching aspects (related to the methods of structuring training actions), but also and above all ethical-political apects, related to the democratization of Higher Education.